Transcendentalism and the cultivation of the soul - Andrews, Barry Maxwell (University of Massachusetts Press, 2017)
American Transcendentalism is often seen as a literary movement--a flowering of works written by New England intellectuals who retreated from society and lived in nature. In Transcendentalism and the Cultivation of the Soul, Barry M. Andrews focuses on a neglected aspect of this well-known group, showing how American Transcendentalists developed rich spiritual practices to nurture their souls and discover the divine. The practices are common and simple -- among them, keeping journals, contemplation, walking, reading, simple living, and conversation. In approachable and accessible prose, Andrews demonstrates how Transcendentalism's main thinkers, Emerson, Thoreau, Fuller, and others, pursued rich and rewarding spiritual lives that inspired them to fight for abolition, women's rights, and education reform. In detailing these everyday acts, Andrews uncovers a wealth of spiritual practices that could be particularly valuable today, to spiritual seekers and religious liberals. -- Provided by publisher.